Renal transplant blood flow in patients with acute tubular necrosis - Huić, Dražen (Radiology and oncology (Ljubljana), 1999)
Background. Since there are contradictions in data, this study was aimed to investigate the quantity of renal transplant blood flow in patients affected by acute tubular necrosis (ATN). Subjects and methods. During the four year period,179 examinations were performed in 60 patients (31 female, 29 male, median age 37 years, range 11-62 years, 42 cadaveric and 18 living related transplants, median follow-up 21 months) using Tc-99m-pertechnetate and 1131-OIH. Renal blood flow was calculated from the first-pass time activity curves generated over the kidney and aorta and expressed as a percentage of cardiac output (RBF/CO). Results. In 53 examinations of the patients with ATN the mean RBF/CO was significantly lower than in 60 examinations of patients with normal graft function (6.5 %+-3.4 %,11.4 %+-3.4 %, respectively, p = 9.6 x 10-12), and similar to the mean values of 49 examinations with acute rejection (AR) and 17 examinations with the combination of ATN and AR (73 %+-3.4 %, 5.8 %+-2.5 %, respectively, p > 0.05). In the patients with ATN meanRBF/CO were significantly related to creatinin serum (CS) value (CS1000 mmol/I - 5.2 % +- 2.2 %, p<0.05) and to 1131 OIH renogram patterns (some OIH excretion from renal parenchyma during the examination - 7.0 %+-3.5 %, no excretion - 5.1%+- 2.2 %, p< 0. 05). Conclusions. Renal transplant blood flow is clearly diminished in ATN, similarly as in AR, and significantly related to the graft function.
Keywords: Blood supply; Graft rejection; Kidney; Kidney transplantation; Kidney tubular necrosis, acute; Radionuclide imaging